Critical Approaches to Security in Europe: A Networked Manifesto - Collective, C.A.S.E. (Security dialogue, 2006)
In the last decade, critical approaches have substantially reshaped the theoretical landscape of security studies in Europe. Yet, despite an impressive body of literature, there remains fundamental disagreement as to what counts as critical in this context. Scholars are still arguing in terms of 'schools', while there has been an increasing and sustained cross-fertilization among critical approaches. Finally, the boundaries between critical and traditional approaches to security remain blurred. The aim of this article is therefore to assess the evolution of critical views of approaches to security studies in Europe, discuss their theoretical premises, investigate their intellectual ramifications, and examine how they coalesce around different issues (such as a state of exception). The article then assesses the political implications of critical approaches. This is done mainly by analysing processes by which critical approaches to security percolate through a growing number of subjects (such as development, peace research, risk management). Finally, ethical and research implications are explored.